2006
DOI: 10.1016/j.jcrs.2006.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Single-piece AcrySof intraocular lens implantation in children with congenital and developmental cataract

Abstract: The 1-piece AcrySof IOL provided satisfactory visual axis clarity, produced an acceptable inflammatory response, and maintained centration in pediatric eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Normally, hydrophobic IOLs are implanted in children [44,45] . A new study from Kleinmann et al [46] has shown similarly good results with the implantation of a hydrophilic IOL in children.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, hydrophobic IOLs are implanted in children [44,45] . A new study from Kleinmann et al [46] has shown similarly good results with the implantation of a hydrophilic IOL in children.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in pediatric cataract surgery without subluxation, the single-piece AcrySof IOL provides satisfactory visual axis clarity, an acceptable inflammatory response, and good centration. 19,20 Konradsen et al 14 implanted a single-piece AcrySof IOL in 62% of pediatric eyes with subluxated cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Trivedi and Wilson 4 report that none of the 25 eyes that had surgery at or after 18 months of age required a second surgery after posterior capsulectomy and vitrectomy and implantation of a 1-piece AcrySof IOL. Nihalani and Vasavada 27 report that in 2-to 6-year-old children, 6 (9.1%) of 20 eyes required a secondary procedure after implantation of 1-piece AcrySof IOLs (with primary posterior capsulectomy, but no vitrectomy). This figure is slightly higher than the 7% Vasavada et al 22 reported after 3-piece AcrySof IOL implantation.…”
Section: Postoperative Outcomes Visual Axis Opacificationmentioning
confidence: 99%
“…Of eyes with a 1-piece AcrySof IOL, synechias developed in 31% that had surgery in the first year of life and 3% that had surgery between 2 years and 6 years of age; no child older than 6 years developed synechias. 20,27 Glistenings Mü llner-Eidenbö ck et al 14 report visually insignificant glistenings in 2 eyes of 1 pediatric patient with an AcrySof IOL. The glistenings were noted 1 week after implantation.…”
Section: Uveal Biocompatibilitymentioning
confidence: 99%